2013
DOI: 10.1063/1.4807734
|View full text |Cite
|
Sign up to set email alerts
|

Realization of an extraordinary transmission window for a seamless Ag film based on metal-insulator-metal structures

Abstract: Articles you may be interested inSimultaneous excitation of multi-spectral surface plasmon resonance using multi-stepped-thickness metallic film Multi-resonant silver nano-disk patterned thin film hydrogenated amorphous silicon solar cells for Staebler-Wronski effect compensation J. Appl. Phys. 116, 093103 (2014); 10.1063/1.4895099In situ optical microspectroscopy approach for the study of metal transport in dielectrics via temperature-and time-dependent plasmonics: Ag nanoparticles in SiO2 films J. Chem. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Figure 4c shows the influence of thickness ( H ) of the SiO 2 dielectric layer on the reflection spectra. There was an obvious redshift with the increasing thickness from 10 nm to 80 nm at the first plasmon resonance, which was opposite to the previously reported results for metal–dielectric–metal nanostructures when changing the interlayer thickness [25]. This opposite shift implies differences in the excitation mechanism between the discussed structure and the other nanostructures.…”
Section: Resultscontrasting
confidence: 92%
“…Figure 4c shows the influence of thickness ( H ) of the SiO 2 dielectric layer on the reflection spectra. There was an obvious redshift with the increasing thickness from 10 nm to 80 nm at the first plasmon resonance, which was opposite to the previously reported results for metal–dielectric–metal nanostructures when changing the interlayer thickness [25]. This opposite shift implies differences in the excitation mechanism between the discussed structure and the other nanostructures.…”
Section: Resultscontrasting
confidence: 92%
“…However, for the structure coated with double PCs, a factor of 16.9 at λ = 1071 nm is achieved, which is three times over that of the Au film with single PC. Comparing the small transmission enhancement in this case with only one Au nanosphere PC, it is reasonable to believe that the obtained optical transparency is with great relevant to the near-perfect optical field extraction by the plasmon modes of the other Au nanosphere PC on the rear side [26]- [28], [33]. As the Au film is sandwiched by double PCs, the excitation of the oscillation electrons [33] on both sides of the metal film is more efficient and could produce efficient light-plasmon interaction with the PCs [33].…”
Section: Proposed Scheme and Its Optical Propertiesmentioning
confidence: 92%
“…2(c). For the rear side PC, as the reciprocal theorem predicts [17], an efficient optical field output-coupling could be achieved via the inverse process [26]- [28] (Fig. 2(d)).…”
Section: Proposed Scheme and Its Optical Propertiesmentioning
confidence: 97%
“…The study of this kind of problems also has a long tradition in the optics and physics communities. Indeed, in recent years, a lot of attention has been paid to 1-D and 2-D metallic periodic structures in connection with the huge interest raised by extraordinary transmission, metasurfaces, and related problems [18]- [23]. A good review of the combined interest of physicists and engineers on this topic can be found in [24].…”
Section: Introductionmentioning
confidence: 99%